Accounting for Foreign Direct Investment: A Professional Accountant’s Judgment - V. S. Levin; E. V. Satalkina (Учёт. Анализ. Аудит, 2022)
The paper is devoted to the research of foreign direct investment accounting in the capital of Russian companies, identifies the similarities and differences in approaches to identifying direct investments in accordance with international and domestic legal norms, detects the problems of inward foreign direct investment accounting and in statistical reports. The subject of the study is the problems of theory and practice of foreign direct investment accounting. The research is based on general scientific principles and research methods: systematization, induction and deduction, synthesis and analysis. Correct identification of direct foreign investments in accounts and reliable disclosure of the accounting information and statistical reporting, at present, causes difficulties for economic entities. The solution to these problems is available through the implementation of the professional judgment of the accountant. The work results having theoretical and applied significance, can be used as a basis for the development of a company’s accounting policy.